Strategi Konten Media Sosial PT Numex Teknologi Indonesia untuk Meningkatkan Brand Awareness - Shelycia, Shelycia; Winata, Angeline (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
Brand awareness is a crucial aspect for a brand to be recognized by the public. This research aims to identify the social media content strategy of PT Numex Teknologi Indonesia in enhancing brand awareness. The study refers to the concept of content marketing by Karr and Moran, as well as brand awareness according to Durianto. This research adopts a descriptive qualitative approach with a case study method. Data were collected through interviews and observation. The results indicate that LandX applies content marketing on social media based on the principles outlined by Karr and Moran. Moreover, these strategies have proven effective in increasing LandX brand awareness. Content analysis of LandX social media was also conducted to support the findings.